The role of chronic blood loss in the pathogenesis of postgastrectomy iron-deficiency anaemia. Issue 10 (October 1970) - Holt, J. M.; Gear, M. W. L.; Warner, G. T.
Abstract : The role of chronic blood loss in the pathogenesis of postgastrectomy iron-deficiency anaemia was assessed by measurements of blood loss over periods of up to three months, using a whole-body counter and 59 Fe. Eleven patients were investigated and eight of these were selected because of a history of iron-deficiency anaemia. Six were shown to be losing blood abnormally, five at a rate of over 150 ml per month. None of the three patients without a history of anaemia lost more than 60 ml per month. At gastroscopy contact bleeding from the mucosa of the gastric remnant was observed in four of the six patients losing blood. The results indicate that in some patients chronic blood loss plays an important role in the pathogenesis of postgastrectomy iron-deficiency anaemia.